Specialization and Competitive Advantages of Leading Processing Industry in South Sumatra - Sony Tian Dhora; Nairobi Nairobi; Arivina Ratih Taher (Jurnal Ekonomi Pembangunan, 2022)
The contribution of the manufacturing sector to the GRDP of South Sumatra Province is 19.72 percent in 2020. A large percentage of GRDP does not necessarily indicate the potential of the processing industry to become a leading sector, so it is necessary to identify the leading processing industry sector. So that this study aims to identify the competitiveness of the leading processing industry sub-sector. The method used are Static Location Quetionts (SLQ), Dynamic Location Quetionts (DLQ), Dispersion Power Index (IDP), Sensitivity Index (IDK) which uses an overlay method to identify sub-sectors of the processing industry. Meanwhile, to determine the competitiveness of the leading processing industry sub-sector is using Shift-Share Dynamic analysis. Using the secondary data sourced from the Indonesia Statistics, the input-output table in 2016 and previous study from 2016-2020. The findings show that from the 16 sub-sectors of the processing industry, there are 3 sub-sectors which include the leading processing industry, namely the food and beverage industry; paper and paper goods industry, printing, and reproduction of recording media; and the chemical, pharmaceutical and traditional medicine industries. Food and beverage industry sub-sector; and the paper industry, and paper goods, printing and reproduction of recording media have competitiveness and specialization. Meanwhile, the chemical, pharmaceutical and traditional medicine industries have no specialization but are competitive.